Trigeminal neuralgia: An overview from pathophysiology to pharmacological treatments. (January 2020) - Gambeta, Eder; Chichorro, Juliana G.; Zamponi, Gerald W.
The trigeminal nerve (V) is the fifth and largest of all cranial nerves, and it is responsible for detecting sensory stimuli that arise from the craniofacial area. The nerve is divided into three branches: ophthalmic (V1), maxillary (V2), and mandibular (V3); their cell bodies are located in the trigeminal ganglia and they make connections with second-order neurons in the trigeminal brainstem sensory nuclear complex. Ascending projections via the trigeminothalamic tract transmit information to the thalamus and other brain regions responsible for interpreting sensory information. One of the most common forms of craniofacial pain is trigeminal neuralgia. Trigeminal neuralgia is characterized by sudden, brief, and excruciating facial pain attacks in one or more of the V branches, leading to a severe reduction in the quality of life of affected patients. Trigeminal neuralgia etiology can be classified into idiopathic, classic, and secondary. Classic trigeminal neuralgia is associated with neurovascular compression in the trigeminal root entry zone, which can lead to demyelination and a dysregulation of voltage-gated sodium channel expression in the membrane. These alterations may be responsible for pain attacks in trigeminal neuralgia patients. The antiepileptic drugs carbamazepine and oxcarbazepine are the first-line pharmacological treatment for trigeminal neuralgia. Their mechanism of action is a modulation of voltage-gated sodium channels, leading to a decrease in neuronal activity. Although carbamazepine and oxcarbazepine are the first-line treatment, other drugs may be useful for pain control in trigeminal neuralgia. Among them, the anticonvulsants gabapentin, pregabalin, lamotrigine and phenytoin, baclofen, and botulinum toxin type A can be coadministered with carbamazepine or oxcarbazepine for a synergistic approach. New pharmacological alternatives are being explored such as the active metabolite of oxcarbazepine, eslicarbazepine, and the new Nav1.7 blocker vixotrigine. The pharmacological profiles of these drugs are addressed in this review.